Hubungan Efisiensi Pengadaan Belanja Modal dan Belanja Pemeliharaan terhadap Kualitas Pengelolaan Barang Milik Negara pada Kementerian/Lembaga - Nurhani, Meirza; Zen, Fauziah (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2023)
The aims of this study is to measure efficiency of the procurement of capital expenditures and maintenance expenditures on the quality of state asset management at Ministries/Agencies (state institutions) based on the Budget Realization document in the 2019 and 2020 budget periods. The paper also analyzes the factors that may affect the efficiency level at the budget preparing stage with reference to State Asset Needs Planning. The research uses the Data Envelopment Analysis (DEA) method to measure efficiency. The efficiency values are then employed in a panel data regression to estimate the determinant factors of the efficiency. The results showed that the efficiency of capital expenditure procurement in 79 state institutions in 2019 and 2020 has an average score of 0.9957 and 0.9927. Meanwhile, the efficiency of maintenance spending in 79 state institutions in 2019 and 2020 had an average score of 0.9855 and 0.9711. Based on the results of panel data regression analysis, the determinant variables - drawn from state institutions' characteristics- and the State Asset Needs Planning document do not significantly influence the state institutions' efficiency in the budgeting process.